Half-spectral analysis of spatial-temporal data: The case study of Iranian daily wind speed data. Issue 3 (9th March 2020) - Shahnavaz, Ali; Mosammam, Ali M.; Behzadi, Mohammad Hassan
Abstract: In this paper, we first study the theory of the spatial-temporal half spectral modeling and describe some properties of recently proposed half spectral models. Next, we propose an estimation method for the estimation of spatial-temporal covariance functions in the half-spectral setting. To assess the performance of the proposed half-spectral models, we conduct two simulations, in which we compare the proposed fitting approach with respect to the other classical estimation methods. The proposed methods have great success in fitting parametric space-time covariance functions specifically for massive data sets. Finally, we apply the proposed methods for a real daily wind speed data in Iran.